2006
DOI: 10.1002/nau.20250
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of levator trauma: A comparison between palpation and 4D pelvic floor ultrasound

Abstract: Palpation of the pubovisceral muscle correlates poorly with 3D/4D pelvic floor ultrasound imaging for the assessment of muscular defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 19 publications
3
69
0
11
Order By: Relevance
“…The authors found poor agreement between the two methods and concluded that imaging has a higher reliability than vaginal palpation, even when performed by a trained and experienced physiotherapist. 32 Further studies using perineometry to evaluate the PFM are required to avoid capturing the action of the other muscle groups that form the wall of the abdominopelvic cavity, 33 because an increase in abdominal pressure will affect the urethral, vaginal and rectal pressures. 34 However, Perschers et al assessed the effect of contraction of the abdominal muscles concomitant with the pelvic floor and reported no significant increase in readings during digital palpation, perineometry, electromyography or ultrasound.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The authors found poor agreement between the two methods and concluded that imaging has a higher reliability than vaginal palpation, even when performed by a trained and experienced physiotherapist. 32 Further studies using perineometry to evaluate the PFM are required to avoid capturing the action of the other muscle groups that form the wall of the abdominopelvic cavity, 33 because an increase in abdominal pressure will affect the urethral, vaginal and rectal pressures. 34 However, Perschers et al assessed the effect of contraction of the abdominal muscles concomitant with the pelvic floor and reported no significant increase in readings during digital palpation, perineometry, electromyography or ultrasound.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Furthermore, transabdominal ultrasound imaging has been found to be more sensitive than digital palpation for the detection of an elevating pelvic floor muscle contraction. 31 In a study by Dietz et al, 23 4-dimensional transperineal ultrasound imaging (eg, real-time 3-dimensional imaging) was found to be more sensitive for detection of defects in the levator ani than digital palpation. Although asymmetries of the bladder base have been observed using conventional 2-dimensional transabdominal ultrasound imaging, there is a need for further studies that correlate…”
Section: Qualitative Evaluation T He Use Of Ultrasound Imagingmentioning
confidence: 99%
“…Easy imaging of pelvic floor seems to be very important in pelvic floor disorders, since about 10% of females with pelvic prolapse have structural defects of the levator ani that cannot be discovered through a physical examination (23,24).…”
Section: Ultrasonografia 3d/4dmentioning
confidence: 99%
“…Lo stato funzionale del pavimento pelvico è un elemento di grande importanza, poiché circa il 10% delle pazienti con prolasso presenta difetti strutturali dell'elevatore dell'ano che sono mal evidenziabili con il PC test (23,24).…”
Section: Advanced Diagnostic Testing For Female Pelvic Floor Dysfunctunclassified